Sustainable Skies: How the Airline Industry is Addressing Climate Change - Leamon, Melissa A.; Rincon, Edwin J.; Robillard, Nichole M.; Sutherland, James J. (Journal of Strategic Innovation and Sustainability, 2019)
The aviation industry is a major emitter of greenhouse gases, which contribute to climate change and ultimately create weather patterns that adversely affect the airlines’ performance and efficiency. This paper provides an overview of the ways in which the airlines are both impacting and impacted by the climate, with recommendations on how industry leaders might create a more sustainable future for aviation. The primary target of this paper is the environmental policy-maker, however, aviation and sustainability enthusiasts may find useful ideas in the paper.